CLINICAL AND SONOGRAPHIC ASSESSMENT OF SYNOVITIS ACTIVITY IN PATIENTS WITH KNEE OSTEOARTHRITIS DURING THERAPY - A. V. Petrov; A. A. Zayaeva (Научно-практическая ревматология, 2016)
The inflammatory process in the synovial membrane (SM), which may be a main cause of chronic pain in many patients, is one of the most significant components in the pathogenesis of osteoarthritis (OA).Objective: to study the time course of clinical and sonographic changes in patients with knee OA who used different symptomatic slow-acting agents, such as chondroitin sulfate (CS), glucosamine sulfate (GS), and diacerein, during an 18-month follow-up period in general clinical practice.Subjects and methods. The investigation enrolled 86 knee OA patients who took CS and/or GS in combination with nonsteroidal anti-inflammatory drugs (NSAIDs) and/or paracetamol in an outpatient setting for 12 months. Clinical and ultrasound (US) studies of the affected knee joints (KJ) were performed at the study inclusion and 12 and 18 months after follow-up initiation. The signs of active synovitis were considered to be increased synovial thickness of up to at least 3 mm and articular fluid accumulation, as evidenced by KJ US study. After 12 months, 36 patients in whom the clinical and sonographic signs of active synovitis persisted were divided into two groups: 1) 19 patients took diacerein instead of CS/GS for the following 6 months; 2) 17 patients in whom the treatment regimen remained unchanged.Results and discussion. 60.4% of the patients with knee OA were observed to have the sonographic signs of active synovitis, which were weakly correlated with the sizes of osteophytes and the thickness of the hyaline cartilage (r < 0.37). The rate of synovitis decreased to 41.9% during 12-month CS/GS therapy. The patients with persistent sonographically active synovitis had higher visual analogue scale and WOMAC pain scores (p < 0.05), as well as high C-reactive protein levels. They needed the more frequent and longer intake of NSAIDs and paracetamol. During the following 6 months, there was a reduction in the signs of active synovitis, as evidenced by US study, in 78.9 and 6.7% of the patients in Groups 1 and 2, respectively.Conclusion. Among those with knee OA, there was a subgroup of patients with persistent sonographically and clinically active synovitis, whose treatment demonstrated the efficacy of the interleukin-1 antagonist diacerein.